2024
DOI: 10.1002/adfm.202313092
|View full text |Cite
|
Sign up to set email alerts
|

Materials Design Innovations in Optimizing Cellular Behavior on Melt Electrowritten (MEW) Scaffolds

Brenna L. Devlin,
Mark C. Allenby,
Jiongyu Ren
et al.

Abstract: The field of melt electrowriting (MEW) has seen significant progress, bringing innovative advancements to the fabrication of biomaterial scaffolds, and creating new possibilities for applications in tissue engineering and beyond. Multidisciplinary collaboration across materials science, computational modeling, AI, bioprinting, microfluidics, and dynamic culture systems offers promising new opportunities to gain deeper insights into complex biological systems. As the focus shifts towards personalized medicine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 170 publications
0
3
0
Order By: Relevance
“…MEW has been commonly employed to develop scaffolds for 3D cell culture. 41 Several studies have highlighted the significance of the scaffold geometry, including pore size, shape, fiber diameter, and stiffness, as a key factor that can influence cellular behavior. 52,53 In particular, a recent study investigating osteogenesis in hMSCs demonstrated the benefits of using 100 μm square PCL scaffolds fabricated via MEW.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MEW has been commonly employed to develop scaffolds for 3D cell culture. 41 Several studies have highlighted the significance of the scaffold geometry, including pore size, shape, fiber diameter, and stiffness, as a key factor that can influence cellular behavior. 52,53 In particular, a recent study investigating osteogenesis in hMSCs demonstrated the benefits of using 100 μm square PCL scaffolds fabricated via MEW.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 Furthermore, MEW has the capacity to process various materials, including functionalizable polymers and material composites, making it a versatile technique. 41 While MEW has been primarily used for fabricating scaffolds with custom microstructures and mechanical properties that mimic the extracellular matrix, 42–44 this work focuses on integrating defined MEW structures onto the magnetoelastic sensor surface to enhance the sensor's performance in monitoring cell growth. Cells have been previously reported to attach and grow with a non-uniform density across magnetoelastic sensor surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Since scaffold geometry in uences cells, we assessed the impact of reinforcements on deformationprone scaffolds utilizing thin MEW PCL scaffolds with triangular patterns. 45 These scaffolds were chosen due to their susceptibility to delamination and overall di culty in handling, attributed to low layerto-layer adhesion and thin ber diameters. Murine Astrocytes, known for their sensitivity and preference for speci c scaffold geometries like triangular grids, 46,47 were employed for this study to promote cell spreading conducive to proliferation.…”
Section: Standard Cell Culturementioning
confidence: 99%